Incomplete Antibodies May Reduce ABO Cross-Match Incompatibility: A Pilot Study - Mehmet Özen; Soner Yılmaz; Tülin Özkan; Yeşim Özer; Aliye Aysel Pekel; Asuman Sunguroğlu; Günhan Gürman; Önder Arslan (Turkish Journal of Hematology, 2018)
Objective: Any erythrocyte transfusion among humans having type A or B blood groups is impossible due to antibodies causing fatal transfusion complications. A cross-match test is performed to prevent immune transfusion complications before transfusion. Our hypothesis is that the fragment antibody (Fab) part of the antibody (incomplete antibody) may be used to prevent an immune stimulus related to the complete antibody. Therefore, we designed a pilot study to evaluate the effectiveness of these incomplete antibodies using cross-match tests. Materials and Methods: Pepsin enzyme and staphylococcal protein A columns were used to cut anti-A and anti-B monoclonal antibodies and purify their Fab (2) fragments, respectively. An Rh-positive erythrocyte suspension with purified anti-A Fab (2) solution and B Rh-positive erythrocyte suspension with purified anti-B Fab (2) solution were combined correspondingly. Cross-match tests were performed by tube and gel centrifugation methods. The agglutination levels due to the anti-A and anti-B Fab (2) antibodies and their effects on the agglutination normally observed with complete antibodies were then measured. Results: No agglutination for the purified incomplete anti-A Fab (2) with A Rh+ erythrocyte and anti-B Fab (2) with B Rh+ erythrocyte combinations was observed in the tube cross-match tests. These agglutination levels were 1+ in two wells in the gel centrifugation cross-match tests. Fab (2)-treated erythrocytes were also resistant to the agglutination that normally occurs with complete antibodies. Conclusion: We determined that the Fab (2) fragments of antibodies may not only be used to obtain a mild or negative reaction when compared to complete antibodies, but they might also be used for decreasing ABO incompatibility. Incomplete antibodies might be a therapeutic option in autoimmune hemolytic anemia and they may also be used in solid organ or hematopoietic stem cell transplantation. Therefore, we have planned an in vivo study to prove these in vitro findings.